Small oxide‐free vertical‐cavity surface‐emitting lasers with high efficiency and high power. Issue 24 (1st November 2014) - Yang, Xu; Li, Ming Xin; Zhao, Guowei; Freisem, Sabine; Deppe, Dennis G.
Abstract : Data are presented showing high external differential quantum efficiency (DQE) and record‐high output power in vertical‐cavity surface‐emitting lasers (VCSELs) with diameters below 3 µm. Good uniformity and reproducibility are achieved in devices with very small sizes. Over 75% DQEs are measured with maximum output powers of 5, 7.3, 8, 8.7 and 11.6 mW for 1, 1.5, 2, 2.5 and 3 µm diameter VCSELs, respectively.